Iron-Binding Compounds from Agrobacterium spp.: Biological Control Strain Agrobacterium rhizogenes K84 Produces a Hydroxamate Siderophore - Penyalver, Ramón (American Society for Microbiology, 2001)
Iron-binding compounds were produced in various amounts in response to iron starvation by a collection of Agrobacterium strains belonging to the species A. tumefaciens, A. rhizogenes, and A. vitis. The crown gall biocontrol agent A. rhizogenes strain K84 produced a hydroxamate iron chelator in large amounts. Production of this compound, and also of a previously described antibiotic-like substance called ALS84, occurred only in cultures of strain K84 grown in iron-deficient medium. Similarly, sensitivity to ALS84 was expressed only when susceptible cells were tested in low-iron media. Five independent Tn5-induced mutants of strain K84 affected in the production of the hydroxamate iron chelator showed a similar reduction in the production of ALS84. One of these mutants, M8-10, was completely deficient in the production of both agents and grew poorly compared to the wild type under iron-limiting conditions. Thus, the hydroxamate compound has siderophore activity. A 9.1-kb fragment of chromosomal DNA containing the Tn5 insertion from this mutant was cloned and marker exchanged into wild-type strain K84. The homogenote lost the ability to produce the hydroxamate siderophore and also ALS84. A cosmid clone was isolated from a genomic library of strain K84 that restored to strain M8-10 the ability to produce of the siderophore and ALS84, as well as growth in iron-deficient medium. This cosmid clone contained the region in which Tn5 was located in the mutant. Sequence analysis showed that the Tn5 insert in this mutant was located in an open reading frame coding for a protein that has similarity to those of the gramicidin S synthetase repeat superfamily. Some such proteins are required for synthesis of hydroxamate siderophores by other bacteria. Southern analysis revealed that the biosynthetic gene from strain K84 is present only in isolates of A. rhizogenes that produce hydroxamate-type compounds under low-iron conditions. Based on physiological and genetic analyses showing a correlation between production of a hydroxamate siderophore and ALS84 by strain K84, we conclude that the two activities share a biosynthetic route and may be the same compound.